1) Given
![f(x) = x^(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/oqeboo28rjd26kz68cc0eqcho55jkjdmdi.png)
![f(bx) = (bx)^(3)= b^(3) x^(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/j3q44sh1np07k5eyjzft2codlnsuik4lje.png)
Since (0.5,8) lies on f(bx) ,
![8=b^(3) 0.5^(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/x63iqroz3rdwdz9kttagfemgu8fto9x726.png)
Divide with
on both sides
![b^(3) = (8)/(0.5^(3) )](https://img.qammunity.org/2019/formulas/mathematics/high-school/ypl8mcegxsizjqkklx461epe96fuj3v0tz.png)
= 64
![b=64^{(1)/(3) } = 4](https://img.qammunity.org/2019/formulas/mathematics/high-school/ljy7kubevdbl3qiooi62s75xtu0dphxol8.png)
Hence b=4.
2) Given (1,3) lies on y=f(x) plugin x=1 and y=3
that is f(1) = 3
We can find corresponding point for that in y=-2f(x) by plugging in x=1.
That is y= -2f(1) = -2*3 = -6
Hence point is (1,-6)